Is seaweed extract an elicitor compound? Changing proline content in drought-stressed bean plants - Carvalho, Marcia E.A.; Castro, Paulo R.C.; Gaziola, Salete A.; Azevedo, Ricardo A. (Comunicata Scientiae, 2018)
Abiotic stresses negatively affect crop development and yield. However, the use of seaweed extracts can alleviate production losses through improvement of the antioxidant system and synthesis of compatible osmolytes. The aim of this study was to assess the effects of Ascophyllum nodosum extract on antioxidant response and yield of common bean plants (Phaseolus vulgaris) under drought stress. Therefore, two methods of application (foliar spray and soil irrigation) and two doses (5 and 10 mL L-1) were tested, whereas untreated plants were used as control. There were no significant differences in malondialdehyde and hydrogen peroxide contents among treatments, indicating that application of seaweed extract did not change the oxidative status in treated plants when compared to the control ones. On the other hand, the use of seaweed extract increased proline content even prior to drought stress (46.3 to 145.4% when compared to the control), and this increment remained until the 10th day of stress (from 60.1 to 201.7% over the reference plants), supporting early evidences that A. nodosum extract is a plant elicitor. The yield parameters were not affected by the extract, probably due to the severe drought stress which plants were submitted. The results suggest that A. nodosum extract affects proline metabolism in Phaseolus vulgaris plants, making the synthesis of this osmolyte more responsive to drought stress because seaweed-treated plants presented a higher proline content than the control ones during the exposure to water deficit.